PRODUCTIVITY OF AGROCENOSES OF CEREAL AND LEGUME CROPS UNDER THE INFLUENCE OF THE BASIC TILLAGE AND MICROFERTILIZERS DURING IRRIGATION IN THE CONDITIONS OF THE DRY-STEPPE VOLGA REGION - Vera E. Kizhaeva; Viktoria O. Peshkova; Vladimir A. Shadskikh (Мелиорация и гидротехника)
Purpose: to conduct research dedicated to assessing the impact of primary soil cultivation techniques and the microelements application on the yield of cereal and leguminous grain crops. Materials and methods. The effect of moldboard plowing (25–27 cm), flat-cutting (20–22 cm), minimum surface tillage (8–10 cm) and no-tillage on the yield of leguminous crops (soybeans, peas, chickpeas) and cereal grains (spring wheat, Sudan grass) is studied. The studies were conducted at the experimental production farm of the Volga Research Institute of Hydraulic Engineering and Land Reclamation in 2022–2024 using generally accepted methods. Results. The impact of basic tillage techniques and the impact of micro-fertilizers on vegetation in cereal and leguminous crops agrocenoses on productivity and its structure have been studied. The use of flat-cutting and the micronutrients application for cereals and legumes increased the yield indicators on average for soybeans – by 65.9 %, peas – 48.5 %, chickpeas – 41.8 %, spring wheat – 61.3 %, Sudan grass – 26.3 % compared with the no-tillage option. The maximum yield was obtained on soybeans with the use of flat-cutting tillage – 3.45 t/ha, and the minimum at no-tillage – 1.94 t/ha. The impact of flat-cutting tillage on the spring wheat productivity is expressed by an increase in yield by 0.34 t/ha, compared with no-tillage. Chickpea yield is higher when using flat-cutting tillage with leaf dressing – 2.75 t/ha, and without tillage and dressing – 1.87 t/ha. The yield of Sudan grass of two staves when using flat cutting tillage with the micronutrients application on vegetation is 40.37 t/ha and 31.50 t/ha with no-tillage. Conclusions. For the soil and climatic conditions of the dry steppe Volga region, it has been proven that when cultivating chickpeas, soybeans, peas, Sudan grass and spring wheat as examples, the best indicators of the crop structure were achieved in variants using flat-cutting tillage against the background of the micronutrients application to vegetative plants.